Ebola salience, death-thought accessibility, and worldview defense: A terror management theory perspective. Issue 9 (21st October 2017) - Arrowood, Robert B.; Cox, Cathy R.; Kersten, Michael; Routledge, Clay; Shelton, Jill Talley; Hood, Ralph W.
ABSTRACT: According to terror management theory, individuals defend their cultural beliefs following mortality salience. The current research examined whether naturally occurring instances of death (i.e., Ebola) correspond to results found in laboratory studies. The results of two experiments demonstrated that participants experienced a greater accessibility of death-related thoughts in response to an Ebola prime during a regional outbreak. Study 2 also showed that increased mortality awareness following an Ebola manipulation was associated with greater worldview defense (i.e., religious fundamentalism). Together, these results suggest that reminders of death in the form of a disease threat operate similarly to a mortality salience manipulation.